Immune-mediated cholangiopathies in children: the need to better understand the pathophysiology for finding the future possible treatment targets - Grama, Alina; Mititelu, Alexandra; Sîrbe, Claudia; Benţa, Gabriel; Pop, Tudor Lucian (Frontiers in Immunology, 2023)
Cholangiopathies are defined as focal or extensive damage of the bile ducts. According to the pathogenetic mechanism, it may be immune-mediated or due to genetic, infectious, toxic, vascular, and obstructive causes. Their chronic evolution is characterized by inflammation, obstruction of bile flow, cholangiocyte proliferation, and progression toward fibrosis and cirrhosis. Immune-mediated cholangiopathies comprise primary sclerosing cholangitis (PSC), autoimmune cholangitis and IgG4-associated cholangitis in adults and biliary atresia (BA), neonatal sclerosing cholangitis (NSC) in children. The main purpose of this narrative review was to highlight the similarities and differences among immune-mediated cholangiopathies, especially those frequent in children in which cholangiocyte senescence plays a key role (BA, NSC, and PSC). These three entities have many similarities in terms of clinical and histopathological manifestations, and the distinction between them can be hard to achieve. In BA, bile duct destruction occurs due to aggression of the biliary cells due to viral infections or toxins during the intrauterine period or immediately after birth. The consequence is the activation of the immune system leading to severe inflammation and fibrosis of the extrahepatic biliary tract, lumen stenosis, and impairment of the biliary flow. PSC is characterized by inflammation and fibrosis of intra- and extrahepatic bile ducts, leading to secondary biliary cirrhosis. It is a multifactorial disease that occurs because of genetic predisposition [human leukocyte antigen (HLA) and non-HLA haplotypes], autoimmunity (cellular immune response, autoantibodies, association with inflammatory bowel disease), environmental factors (infections or toxic bile), and host factors (intestinal microbiota). NSC seems to be a distinct subgroup of childhood PSC that appears due to the interaction between genetic predisposition (HLA B8 and DR3) and the disruption of the immune system, validated by elevated IgG levels or specific antibodies [antinuclear antibody (ANA), anti-smooth muscle antibody (ASMA)]. Currently, the exact mechanism of immune cholangiopathy is not fully understood, and further data are required to identify individuals at high risk of developing these conditions. A better understanding of the immune mechanisms and pathophysiology of BA, NSC, and PSC will open new perspectives for future treatments and better methods of preventing severe evolution.